2009
DOI: 10.1002/we.324
|View full text |Cite
|
Sign up to set email alerts
|

The habitat‐creation potential of offshore wind farms

Abstract: Offshore wind farms are the subject of environmental impact assessments in which potential adverse effects are identified and quantified. Those impacts will then require to be mitigated through appropriate design, construction and operation methods. Where environmental impacts cannot be mitigated, operators would be required to compensate the environment or its users for any actual or potential damage. The present study shows that the placement of offshore wind turbines gives the potential for habitat creation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 16 publications
0
69
0
3
Order By: Relevance
“…Gill, 2005;Wahlberg and Westerberg, 2005;Petersen and Malm, 2006;Broström, 2008;Tyack, 2008). At the same time, there is an increasing interest in articulating the potentially positive aspects of creating artificial hard bottom habitats through the construction of offshore renewable energy devices (Wilhelmsson et al 2006a;Langhamer et al, 2009;Wilson and Elliot, 2009). The foundations of the energy devices will exclude trawling activities from the claimed area, and will also constitute "secondary artificial reefs" (Pickering et al, 1998) for fish and invertebrates and may also function as fish aggregating devices (FADs) (Wilhelmsson et al, 2006a;Fayram and de Risi, 2007;Wilhelmsson and Malm, 2008;Langhamer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gill, 2005;Wahlberg and Westerberg, 2005;Petersen and Malm, 2006;Broström, 2008;Tyack, 2008). At the same time, there is an increasing interest in articulating the potentially positive aspects of creating artificial hard bottom habitats through the construction of offshore renewable energy devices (Wilhelmsson et al 2006a;Langhamer et al, 2009;Wilson and Elliot, 2009). The foundations of the energy devices will exclude trawling activities from the claimed area, and will also constitute "secondary artificial reefs" (Pickering et al, 1998) for fish and invertebrates and may also function as fish aggregating devices (FADs) (Wilhelmsson et al, 2006a;Fayram and de Risi, 2007;Wilhelmsson and Malm, 2008;Langhamer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The area of habitat created depends on whether scour protection is installed, and if so, which type of material is used. Wilson and Elliott [6] showed that with synthetic fronds, which mimic seagrass, there is a potential for a direct area loss of 12.5 m 2 ; however when boulder and gravel protection are used, the habitat gain is 577 m 2 and 650 m 2 respectively, assuming a 4 m diameter turbine, and 10 m of scour protection, as above.…”
Section: Seabed Sediments Hydrography and Benthic Invertebratesmentioning
confidence: 95%
“…For example, different impacts are expected to arise from wave energy conversion devices which are floating and anchored (e.g., OPD's Pelamis system (www.pelamiswave.com) in comparison to where these are mounted on the seabed (e.g., the Oyster device of Aquamarinepower). A further, quantitative comparison tool or matrix which allows a better comparison between sectors and activities in the offshore environment has been developed [5,6], and aims to capture many of the offshore activities currently being undertaken, and a wide range of potential impacts on the marine environment, both positive and negative, which might be caused by any of these activities.…”
Section: Moderate Adversementioning
confidence: 99%
See 2 more Smart Citations